Interprofessional non-technical skills for surgeons in disaster response: a literature review. Issue 5 (7th June 2013) - Willems, Anneliese; Waxman, Bruce; Bacon, Andrew K.; Smith, Julian; Kitto, Simon
Abstract: Natural disasters impose a significant burden on society. Current disaster training programmes do not place an emphasis on equipping surgeons with non-technical skills for disaster response. This literature review sought to identify non-technical skills required of surgeons in disaster response through an examination of four categories of literature: "disaster"; "surgical"; "organisational management"; and "interprofessional". Literature search criteria included electronic database searches, internet searches, hand searching, ancestry searching and networking strategies. Various potential non-technical skills for surgeons in disaster response were identified including: interpersonal skills such as communication, teamwork and leadership; cognitive strategies such flexibility, adaptability, innovation, improvisation and creativity; physical and psychological self-care; conflict management, collaboration, professionalism, health advocacy and teaching. Such skills and the role of interprofessionalism should be considered for inclusion in surgical disaster response training course curricula.